ENTHUSIASM OF THE COMMUNITY OF LAMSEUNONG LAMA VILLAGE, KAJHU VILLAGE IN THE EVENT TO COMMEMORATE THE 18TH ANNIVERSARY OF THE TSUNAMI ON DECEMBER 26, 2004 - Sufyan; Tarmizi; Maimun; Riyan Maulana; Muhammad Yassir; Rahmat Arfan; Dara Zulfinar; Adi Ahmad (Jurnal Pengabdian Bangsa, 2023)
Community Service (PKM) is one form of the tridharma of higher education through the dedication of lecturers and students to the community which is also a process of self-maturation by interacting directly with the wider community. Community Service (PKM) is also an effort to realize more efficient education, namely education that is directly experienced by lecturers and students, so lecturers and students do not only get material, but more importantly, the theories obtained in the lecture hall must also be applied in the field, especially in the community environment of Lamseunong Lama Hamlet, Kajhu Village, Baitussalam District, Aceh Besar Regency.